PENGARUH RETURN ON EQUITY (ROE) TERHADAP HARGA SAHAM DENGAN NILAI PERUSAHAAN SEBAGAI VARIABEL INTERVENING PADA PERUSAHAAN YANG BERGABUNG DALAM INDEKS LQ-45 PERIODE 2018-2020 - Qomariyah, Badriyatul; Soeliha, Siti; Pramitasari, Triska Dewi (Jurnal Mahasiswa Entrepreneurship (JME), 2022)
Establishing a company must have a goal, one of which is to improve the welfare of shareholders or company owners. Shareholders want the company to maximize profits so that their welfare is higher, but in the process the profits of a company will not always increase. Therefore, it is necessary to analyze the performance of a company to assess and find out the company's performance, one of which is looking at the company's financial statements. The purpose of this study was to analyze and test the effect of Return On Equity (ROE) on stock prices with firm value as an intervening variable. The population in this study were all companies that joined the LQ45 index in 2018-2020, totaling 45 companies. The sampling method used purposive sampling technique. The sample in this study were 12 companies. Data analysis and hypothesis testing in this study used the Structural Equation Model - Partial Least Square (PLS-SEM). The results of the direct influence hypothesis test using the Smart PLS 3.0 application, show that Return On Equity (ROE) has a significant positive effect on firm value, Return On Equity (ROE) has a significant positive effect on stock prices, firm value has a significant positive effect on stock prices. The results of the indirect influence hypothesis show that the Return On Equity (ROE) variable on stock prices through firm value has a significant positive effect.